Pengaruh Model Pembelajaran Jelajah Alam Sekitar (JAS) Terhadap Hasil Belajar Siswa Kelas VII MTS- AL-Farabi Wasilei Selatan Kabupaten Halmahera Timur - Jena Andres Jena Andres; Ema Jamay (Peneliti.net, 2020)
The learning model is defined as a systematic procedure in organizing learning experiences to achieve learning objectives. So, actually the learning approach has the same meaning as the learning approach or strategy. Currently, various kinds of learning approaches have been developed, from simple to complex and complicated because they require many tools in their application. The approach in the learning process is a method or technique of presenting material used by educators in the learning process to achieve the expected learning objectives. The cooperative learning model is also a learning model which in the organizational strategy uses small study groups where students or students work together for the success of the learning objectives. Cooperative learning is a model in which students learn together, share their thoughts and are responsible for achieving individual and group learning outcomes. JAS learning is a strategy in learning that prioritizes land around the school or other learning resources outside of school so that it allows students to learn directly from the environment. natural phenomena based on his own observations. In this case the teacher must be observant in choosing the appropriate subject matter. The population in this study includes all students of class VII MTs. Alfarabi Wasilei Selatan, East Halmahera Regency with a total of 42 students consisting of 2 classes. The assumption in this study uses the RAL assumption where all initial treatments are considered the same, there is no difference so that the results obtained are absolute because of the influence of the treatment. Based on the results of data analysis and discussion, it can be concluded that there is an effect of the JAS model on student learning outcomes at Mts. Alfarabi Wasilei Selatan, East Halmahera Regency, where based on the results of the ANOVA posttest, a significance value of 0.000 ≤ 0.05 or sig ≤ 0.05 was obtained.